2021
DOI: 10.1124/jpet.121.000723
|View full text |Cite|
|
Sign up to set email alerts
|

The Cannabinoid Receptor Type 1 Positive Allosteric Modulator ZCZ011 Attenuates Naloxone-Precipitated Diarrhea and Weight Loss in Oxycodone-Dependent Mice

Abstract: octadeca-7(18),8,10-trien-14-one; Oxycodone hydrochloride, (5α)-4,5-epoxy-14-hydroxy-3-methoxy-17-methylmorphinan-6-one;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Withdrawal from opioids such as heroin and morphine has been shown to result in hyperalgesia in humans (74,75) and similarly in rats and mice (16,18). Recent studies have shown oxycodone withdrawal to result in increase of mechanical pain sensitivity in rats (10) and somatic withdrawal signs in mice (20)(21)(22). Overall, these prior studies are consistent with the current results from withdrawal from IVSA of fentanyl, suggesting similar withdrawal symptoms across opioids in preclinical studies.…”
Section: Discussionsupporting
confidence: 83%
“…Withdrawal from opioids such as heroin and morphine has been shown to result in hyperalgesia in humans (74,75) and similarly in rats and mice (16,18). Recent studies have shown oxycodone withdrawal to result in increase of mechanical pain sensitivity in rats (10) and somatic withdrawal signs in mice (20)(21)(22). Overall, these prior studies are consistent with the current results from withdrawal from IVSA of fentanyl, suggesting similar withdrawal symptoms across opioids in preclinical studies.…”
Section: Discussionsupporting
confidence: 83%
“…CB1 and µ-opioid receptors are also co-expressed in areas relevant to drug withdrawal(Scavone et al, 2013). CB1 agonists, allosteric modulators and endocannabinoid degradation inhibitors reduce measures of µ-opioid dependence and withdrawal(Lichtman et al, 2001; Schlosburg et al, 2009; Ramesh et al, 2011; Wilkerson et al, 2017; Dodu et al, 2022). In humans, the Δ 9 -THC conjugate dronabinol has been shown to suppress opioid withdrawal signs in opioid-dependent individuals(Bisaga et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that in ZCZ011-treated mice, rimonabant (CB 1 R antagonist), but not SR14428 (CB 2 R antagonist), blocked the protective effect of ZCZ011 on naloxone-induced body mass loss. Further, it was also observed that the protective effects of ZCZ011 in attenuating naloxone-related weight loss were lost entirely in CB 1 R knockout mice, which again solidifies that the mechanism of action of ZCZ011 is CB 1 R mediated [62]. Another study showed that in a mouse model for Huntington’s disease CB 1 R PAMs, GAT211, and GAT229 promoted normal weight gain and increased body fat content in R8/2 mice, which is critical, as patients suffering from Huntington’s disease experience a failure to gain weight and body fat content [63].…”
Section: Discussionmentioning
confidence: 82%
“…was administered alone and subcutaneously as compared to previous studies [55,62] where intraperitoneal route was used and ZCZ011 was administered along with a CB1R orthosteric ligand [55]. These differences in the methodologies may have led to only subtle changes in behavior and the endocannabinoid system following chronic ZCZ011 treatment.…”
Section: Discussionmentioning
confidence: 99%